1992
DOI: 10.1037/0882-7974.7.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Age and occupational well-being.

Abstract: Two questions are examined through an investigation of 1,686 people employed in a wide range of jobs. First, is there a U-shaped relationship between age and occupational well-being, such that medium-aged workers report lower well-being than do both younger and older people? That pattern is found, in relationship to both job anxiety-contentment and job depression-enthusiasm. Second, can the observed associations between age and well-being be accounted for by 13 potentially explanatory factors, covering job pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
146
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 28 publications
16
146
1
6
Order By: Relevance
“…Thus, we hypothesized that women, Blacks, and less well-educated workers will report more positive perceptions of how their jobs affect their health. Warr (1992) speculated that individuals from older cohorts enter the labor force feeling more optimistic about employment than their younger cohort counterparts and may "hold onto" this optimism better. Furthermore, the degree of self-selection into the labor force is probably greater among older than younger individuals, so that the sense of optimism about employment among older workers is reinforced by this selection.…”
Section: Health Effects Of Work: Individual Characteristicsmentioning
confidence: 99%
“…Thus, we hypothesized that women, Blacks, and less well-educated workers will report more positive perceptions of how their jobs affect their health. Warr (1992) speculated that individuals from older cohorts enter the labor force feeling more optimistic about employment than their younger cohort counterparts and may "hold onto" this optimism better. Furthermore, the degree of self-selection into the labor force is probably greater among older than younger individuals, so that the sense of optimism about employment among older workers is reinforced by this selection.…”
Section: Health Effects Of Work: Individual Characteristicsmentioning
confidence: 99%
“…The aforementioned control variables were chosen because they have been shown to be associated with both evaluations of ethical culture (e.g., Huhtala et al, 2011) and occupational well-being (e.g., van der Hulst, 2003;Warr, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, older employees are less likely to leave and remain more contended in their current job (Warr, 1992;Doering et al, 1983;Glenn et al, 1977). Some studies indicated a positive correlation between age and satisfaction but others reported a U-shaped relationship (Petrides & Furnham, 2006).…”
Section: Job Satisfaction and Agementioning
confidence: 99%